Potential Pathophysiological Mechanisms Underlying Multiple Organ Dysfunction in Cytokine Release Syndrome - Chen, Peixian; Tang, Yan; He, Weixin; Yang, Ruixuan; Lan, Zhien; Chen, Ruirong; Zhang, Peidong (Mediators of Inflammation, 2022)
In recent decades, many serious respiratory infections have broken out all over the world, including SARS-CoV, MERS, and COVID-19. They are characterized by strong infectivity, rapid disease progression, high mortality, and poor prognosis. Excessive immune system activation results in cytokine hypersecretion, which is an important reason for the aggravation of symptoms, and can spread throughout the body leading to systemic multiple organ dysfunction, namely, cytokine release syndrome (CRS). Although many diseases related to CRS have been identified, the mechanism of CRS is rarely mentioned clearly. This review is intended to clarify the pathogenetic mechanism of CRS in the deterioration of related diseases, describe the important signaling pathways and clinical pathophysiological characteristics of CRS, and provide ideas for further research and development of specific drugs for corresponding targets to treat CRS.